Carboxylation of Alkenes with CO2 via Photocatalytic Cleavage of C=C Double Bonds - Yuan, Pan-Feng; Meng, Qing-Yuan (Synlett, 2024)
The cleavage of double bonds in alkenes constitutes an integral process in converting feedstock materials into high-value synthetic intermediates. Well-known examples such as the oxidative cleavage of olefins and olefin metathesis only facilitate the synthesis of oxygen-containing compounds and the recombination of olefins. Therefore, it is appealing to extend C=C double bond cleavage to yield more abundant transformations. Herein, we report a novel photocatalytic approach for the deconstructive carboxylation of alkenes with CO2 for the synthesis of carboxylic acids in the absence of transition metals. Compared with reported carboxylations with CO2 during which carbon numbers are typically increased, we achieve the exchange of carbon dioxide with one of the carbons of the alkene double bond, thus providing carboxylic acids with unchanged carbon numbers when terminal alkenes are used.
Keywords: alkenes; carbon dioxide; carboxylation; photocatalysis; synthetic methods